Realiasasi Spirit Entreprenuership melalui Website Berbasis E-Commerce di kalangan Mahasiswa (Studi Pada Mahasiswa Jurusan Syariah dan Ekonomi Islam IAIN Kudus) - Rohmah, Farida (BISNIS, 2018)
This research is motivated by the increasing number of unemployed college graduates, because more of them want to become office employees or state employees. In fact, there are opportunities that can be made to become new fields of work. Their mindset must be changed so that they do not become government spending to create jobs. Therefore, from now on it is necessary to introduce entrepreneurial education, so that their entrepreneurial spirit develops well. One of the objectives of giving this course is the formation of an entrepreneurial spirit. The purpose of this study is from a course program that can provide knowledge for college graduates about the world of business, and form a mindset to seriously become entrepreneurs. This research is descriptive qualitative and provides a real picture related to the competency of entrepreneurship courses in IAIN Kudus for students and the effect of the realization of E-commerce utilization on student activities in becoming young entrepreneurs. E-commerce is the process of buying and selling transactions that use electronic devices such as telephone and internet. E-commerce is more than just buying and selling products online but includes all the processes of developing, marketing, selling, shipping, servicing and paying for customers and customers, with support from business partners around the world. This system relies heavily on internet resources and other technologies that can support this process. These results can be developed along with the level of need, because entrepreneurial subjects will increase along with the business world. the increasing competency in improving the spirit of young entrepreneurs is expected in the micro scope to increase the entrepreneur's bargaining position and in the macro scope to be able to economy development.